Evidential Value That Exercise Improves BMI z-Score in Overweight and Obese Children and Adolescents - Kelley, George A. (Biomed Res Int, 2015)
Background. Given the cardiovascular disease (CVD) related importance of understanding the true effects of exercise on adiposity in overweight and obese children and adolescents, this study examined whether there is evidential value to rule out excessive and inappropriate reporting of statistically significant results, a major problem in the published literature, with respect to exercise-induced improvements in BMI z-score among overweight and obese children and adolescents. Methods. Using data from a previous meta-analysis of 10 published studies that included 835 overweight and obese children and adolescents, a novel, recently developed approach (p-curve) was used to test for evidential value and rule out selective reporting of findings. Chi-squared tests (χ (2)) were used to test for statistical significance with alpha (p) values <0.05 considered statistically significant. Results. Six of 10 findings (60%) were statistically significant. Statistically significant right-skew to rule out selective reporting was found (χ (2) = 38.8, p = 0.0001). Conversely, studies neither lacked evidential value (χ (2) = 6.8, p = 0.87) nor lacked evidential value and were intensely p-hacked (χ (2) = 4.3, p = 0.98). Conclusion. Evidential value results confirm that exercise reduces BMI z-score in overweight and obese children and adolescents, an important therapeutic strategy for treating and preventing CVD.